Begonia bachulkarii (Begoniaceae, sect. Reichenheimia), a new species from the southern Western Ghats with notes on sect. Reichenheimia in India - Aitawade, Makarand Mohanrao; Kattukunnel, Joseph John; Yadav, Shrirang Ramchandra (Phytotaxa, 2019)
A new species of Begonia, B. bachulkarii has been described from the southern Western Ghats of India, which appears to be a narrow endemic restricted to its type locality. It is closely allied to B. floccifera. Morphological similarities and differences between both species and with the remaining species of sect. Reichenheimia from India are discussed. An artificial key is provided for the identification of species of sect. Reichenheimia from India.